Microglial pyroptosis as a therapeutic target after traumatic spinal cord injury: current progress and future directions - Shi, Lei; Qian, Qiheng; Xie, Jiding; Yang, Taoshuo; Zhao, Xinyu; Meng, Xiangqi; Dai, Jingang; Jin, Qiguan (Frontiers in Immunology, 2025)
Traumatic spinal cord injury (TSCI) is a devastating neurological condition with limited therapeutic options and a high likelihood of permanent disability. Among the multifaceted secondary injury mechanisms triggered by TSCI, pyroptosis—an inflammatory form of programmed cell death—has emerged as a key pathological process. In particular, microglial pyroptosis plays a pivotal role in exacerbating neuroinflammation and disrupting tissue homeostasis, thereby amplifying the secondary injury cascade. This review provides a comprehensive overview of the molecular pathways mediating microglial pyroptosis, including canonical (NLRP3–caspase-1–GSDMD), non-canonical (caspase-11–GSDMD), and atypical (caspase-3/8–GSDME/GSDMC) signaling. We also examine recent therapeutic strategies aimed at suppressing microglial pyroptosis—such as extracellular vesicle-based delivery systems, small-molecule compounds, and gene-targeted approaches—and assess their potential to enhance neurological and motor recovery following SCI. By elucidating both the pathological significance and therapeutic promise of microglial pyroptosis, this review offers novel perspectives on its translational potential as a target for spinal cord injury intervention.